Development of a 3D in vitro human-sized model of cervical dysplasia to evaluate the delivery of ethyl cellulose-ethanol injection - Cadena, Ines A.; Adhikari, Gatha; Almer, Alyssa; Jenne, Molly; Obasi, Ndubuisi; Soria Zurita, Nicolas F.; Rochefort, Willie E.; Mueller, Jenna L.; Fogg, Kaitlin C. (Frontiers in Biomaterials Science, 2024)
Introduction: Cervical cancer, the second leading cause of cancer-related death for women worldwide, remains a preventable yet persistent disease that disproportionately affects women in low and middle-income countries (LMICs). While existing therapies for treating cervical dysplasia are effective, they are often inaccessible in LMICs. Ethanol ablation is an alternative low-cost, accessible therapy that we previously enhanced into ethyl cellulose (EC)-ethanol gel formulation to improve efficacy. Methods: To evaluate the efficacy of EC-ethanol, in this study, we developed a 3D in vitro model of cervical dysplasia featuring a central lesion of cervical cancer cells surrounded by fibroblasts and keratinocytes. Using a GelMA hydrogel formulation (8.7% w/v), we successfully built a 3D model that captured the architectural complexity of cervical dysplasia. We evaluated changes in cell coverage and cell viability. Then, we compared the viscoelastic properties of the GelMA hydrogels to human cervical tissue and using micro-CT imaging, we assessed EC-ethanol injection deposition in the hydrogel, revealing retention of virtually the entire injected volume near the injection site. Finally, we measured changes in cell viability and cell coverage after the EC-ethanol injection. Results: The developed 3D in vitro model successfully replicated the architectural complexity of cervical dysplasia, demonstrating high cell viability and capturing cell responses effectively. The GelMA hydrogel formulation (8.7% w/v) exhibited viscoelastic properties akin to human cervical tissue. Micro-CT imaging revealed efficient deposition of EC-ethanol within the hydrogel, with retention of the injected volume near the injection site. Furthermore, the EC-ethanol injection significantly reduced cervical cancer cell viability and cell coverage while preserving healthy cells within the model. Conclusion: Our findings indicate that our 3D in vitro model mirrored the architecture of cervical dysplasia and demonstrated the potential of EC-ethanol for localized treatment of cervical dysplasia.